CATÁLOGO DE LA COLECCIÓN DE PAPAYA SERRANA (Vasconcellea pubescebs A. DC.) - Medina Loayza, Jorge Vicente; Valdez Alfaro, Ike Alan; Chávez Galarza, Julio César (Instituto Nacional de Innovación Agraria, 2021)
85 páginas